The Problem of Theatrical Autonomy - Edelman, Joshua, 1978- (Amsterdam University Press, 2016)
As any devoted theatregoer will attest, watching a performance is a unique experience, as the social setting, rules, and standards of theatre often combine to create a feeling of liberation from the everyday world. This book explores the phenomenon of theatre as simultaneously distinct from and yet connected to society as a whole. Combining theoretical reflections with materials from European case studies, the authors offer intriguing new methods for the sociological study of theatre while contributing equally to theatre and performance studies.